Home ownership, housing policy and path dependence in Finland, Norway and Sweden - Bo Bengtsson; Hannu Ruonavaara; Jardar Sørvoll (Edward Elgar Publishing, 2022)
Although home ownership is the dominant housing tenure in practically all countries, discussions on housing policy and politics tend to focus on the rental tenure, both in universal and selective housing regimes. To some extent, home ownership seems to be defined as being outside housing policy and, at the most, subject to intended or unintended effects of overarching economic, financial and taxation policies. Starting from Jim Kemeny’s idea of a socially constructed ‘myth of homeownership’, this paper discusses the characteristics and potentials of a housing policy that includes home ownership, and what specific expressions the well-known institutional and discursive path dependence of housing provision would take within such a policy. The argument is illustrated with observations from three Nordic housing regimes (Sweden, Norway and Finland), where home-ownership has been seen as an important ingredient in general housing policies, although from different cultural and ideological standpoints. Sweden where owner occupation has not been that common but so-operative housing has been important has until recently pursued universal, tenure neutral policies.  However, this has been changing in recent system change. In Norway the “myth of home ownership” has been strong, and social democratic housing policies have provided universal support for home ownership and co-operative tenure.  Norwegian housing regime has since the 1980s developed towards a dualist system with unregulated owner occupied and private rental markets and a small targeted municipal sector.  In Finland where home ownership has dominated the past selective housing policies operated through both home ownership and renting. In recent times the focus has shifted towards social rental housing.  We also discuss to what extent the recent housing and financial crisis can be seen as a ’critical juncture’ in the role of homeownership in the three countries.
Housing Wealth and Welfare